2023
DOI: 10.3390/nu15224778
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trials to Treat Obesity in Military Populations: A Systematic Review and Meta-Analysis

Davide Gravina,
Johanna Louise Keeler,
Melahat Nur Akkese
et al.

Abstract: In recent years, overweight and obesity have reached an alarmingly high incidence and prevalence worldwide; they have also been steadily increasing in military populations. Military personnel, as an occupational group, are often exposed to stressful and harmful environments that represent a risk factor for disordered eating, with major repercussions on both physical and mental health. This study aims to explore the effectiveness of weight loss interventions and assess the significance of current obesity treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…A systematic review and meta-analysis of randomized controlled trials to treat obesity in military populations was performed by Gravina et al [ 16 ]. They found that the current weight loss interventions are effective in military populations with a high level of evidence for physical activity, dietary and nutritional interventions, cognitive behavioral therapy, and structured outcome monitoring (clinical or self-monitoring).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis of randomized controlled trials to treat obesity in military populations was performed by Gravina et al [ 16 ]. They found that the current weight loss interventions are effective in military populations with a high level of evidence for physical activity, dietary and nutritional interventions, cognitive behavioral therapy, and structured outcome monitoring (clinical or self-monitoring).…”
mentioning
confidence: 99%
“…The GDF-15 receptor GFRAL, which is known to be involved in appetite regulation, was found to be expressed across various central-nervous as well as peripheral tissues [ 12 ], and visfatin, S100B, and leptin are associated with the development of metabolic syndrome in people with bipolar depression [ 13 ]. Four articles of this Special Issue [ 14 , 15 , 16 , 17 ] summarized already available (e.g., nutritional interventions, psychological and family therapy) [ 14 ] and experimental (smart toy Purrble) [ 15 ] therapies for AN, effective therapies for the treatment of obesity (e.g., physical activity, dietary and nutritional intervention, cognitive behavioral therapy, clinical and self-monitoring) [ 16 ], as well as the preventive and therapeutic options for oral health consequences of EDs [ 17 ]. Witaszek et al’s finding that liraglutide and semaglutide were associated with increased cognitive restraint [ 8 ] is also therapeutically relevant as these GLP-1 receptor agonists are approved for the treatment of obesity.…”
mentioning
confidence: 99%